NKp30 and NKG2D contribute to natural killer cell-mediated recognition of HIV-infected cells - Pi, Ruoxi; Zhao, Nancy Q.; Bien, Allison J.; Ranganath, Thanmayi; Seiler, Christof; Holmes, Susan; Marson, Alexander; Nguyen, David N.; Blish, Catherine A. (iScience, 2025)
Natural killer (NK) cells respond rapidly in early HIV-1 infection. HIV-1 prevention and control strategies harnessing NK cells could be enabled by mechanistic understanding of how NK cells recognize HIV-infected T cells. Here, we profiled the phenotype of human primary NK cells responsive to autologous newly HIV-infected CD4 T cells in vitro. We characterized the patterns of NK cell ligand expression on CD4 T cells at baseline and after infection with a panel of transmitted/founder HIV-1 strains to identify key receptor-ligand pairings. CRISPR editing of CD4 T cells to knock out the NKp30 ligand B7-H6, or the NKG2D ligand MICB reduced NK cell responses to HIV-infected cells in some donors. Blockade of NKp30 or NKG2D on NK cells compromised their specificity of killing HIV-infected cells. Collectively, we identified receptor-ligand pairs including NKp30:B7-H6 and NKG2D:MICB that contribute to NK cell recognition of HIV-infected cells. [Display omitted] •Ligands of NKp30 and NKG2D are upregulated on HIV-infected CD4 T cells•Ligand expression varies more between individuals than between viral strains•NKp30 and NKG2D facilitate HIV-specific cytotoxicity mediated by NK cells Natural sciences; Biological sciences; Immunology; Immunity